A rotina como categoria pedagógica e as implicações da pandemia do COVID-19 na vida das crianças: experiências no estágio supervisionado na educação infantil. - GOMES, Hevelin Taiana Aviz (2023)
This experience report is the result of Supervised Internship in Early Childhood Education, carried out in a Jardim II class in the year 2021, at E.M.E.I Claudia Bethânia Ferreira Cavaleiro de Macedo. Its objective is to address the importance of internship in the academic formation of future educators, emphasizing how necessary it is to experience the teaching process in the formation journey. In light of this context, the report presents a qualitative approach methodology with an exploratory and investigative nature. During the fieldwork, observation was employed, with observations being recorded in a field diary. The results indicate that the internship provided significant theoretical and practical insights into the importance of pedagogical routines for the development of Early Childhood children. It also reflects how the pandemic affected the school environment, pointing out the adaptations implemented to ensure the children's safety. Thus, we emphasize the importance of internship as an enriching and bidirectional experience, where educators and children learn from each other. The report highlights the complexity of Early Childhood Education and the need to adapt practices to meet the needs of each child, underscoring the crucial role of educators in building an effective and meaningful learning environment.